2021
DOI: 10.3390/cancers13133333
|View full text |Cite
|
Sign up to set email alerts
|

Possible Therapeutic Strategy Involving the Purine Synthesis Pathway Regulated by ITK in Tongue Squamous Cell Carcinoma

Abstract: The epidermal growth factor receptor is the only available tyrosine kinase molecular target for treating oral cancer. To improve the prognosis of tongue squamous cell carcinoma (TSCC) patients, a novel molecular target for tyrosine kinases is thus needed. We examined the expression of interleukin-2–inducible T-cell kinase (ITK) using immunohistochemistry, and the biological function of ITK was investigated using biochemical, phosphoproteomic, and metabolomic analyses. We found that ITK is overexpressed in TSCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The folate cycle provides methyl groups for various cellular pathways including DNA methylation. Some studies have reported that drugs directly affect the expression of GART, further regulating processes such as DNA methylation and metabolism, finally leading to the inhibition of cell proliferation. , There was also indirect modulation of GART by affecting the growth level of cancer cells. , Studies on colorectal cancer have identified a new method for MSI genotyping, which improves the detection of microsatellite instability (MSI) affecting single-nucleotide repeats using MALDI-TOF-MS for guiding the molecular diagnosis of hereditary nonpolyposis colorectal cancer syndrome (HNPCC), including the study of the GART gene. In addition, proteomic and metabolomic analyses using the UPLC-MS platform to reveal the overall response for drug treatment with Shikonin, finding that GART was reduced in the Shikonin-treated group, demonstrating the antitumor effects mediated by Shikonin in a human-derived tumor tissue xenograft model (PDX) mouse of colorectal cancer .…”
Section: Resultsmentioning
confidence: 99%
“…The folate cycle provides methyl groups for various cellular pathways including DNA methylation. Some studies have reported that drugs directly affect the expression of GART, further regulating processes such as DNA methylation and metabolism, finally leading to the inhibition of cell proliferation. , There was also indirect modulation of GART by affecting the growth level of cancer cells. , Studies on colorectal cancer have identified a new method for MSI genotyping, which improves the detection of microsatellite instability (MSI) affecting single-nucleotide repeats using MALDI-TOF-MS for guiding the molecular diagnosis of hereditary nonpolyposis colorectal cancer syndrome (HNPCC), including the study of the GART gene. In addition, proteomic and metabolomic analyses using the UPLC-MS platform to reveal the overall response for drug treatment with Shikonin, finding that GART was reduced in the Shikonin-treated group, demonstrating the antitumor effects mediated by Shikonin in a human-derived tumor tissue xenograft model (PDX) mouse of colorectal cancer .…”
Section: Resultsmentioning
confidence: 99%
“…We examined the formalin-fixed paraffin-embedded (FFPE) surgical tissue specimens of 40 patients with TSCC who underwent glossectomy alone with curative intent for stage-I/-II TSCC at the National Cancer Center (NCC) Hospital, Tokyo, Japan, between 1999 and 2011 [17]. Follow-up was conducted between 2000 and 2017 (median, 78.05 months; range, 7.2-188.4 months).…”
Section: Patients and Tissue Samplesmentioning
confidence: 99%
“…Tumor histological type was classified according to the International Union Against Cancer (UICC) TNM Classification of Malignant Tumors, 8th edition. Histological grading was performed as described previously [17].…”
Section: Patients and Tissue Samplesmentioning
confidence: 99%
“… 3 In recent years, some progress has been made in the surgery, radiotherapy, chemotherapy, and immunotherapy of TSCC. 4 6 However, the overall survival rate of patients with locally advanced tumors and cervical lymph node metastasis remains low. 7 For patients who receive radical surgery, major surgical trauma can cause damage to swallowing, speech, and even breathing functions, leading to a severe decline in quality of life.…”
Section: Introductionmentioning
confidence: 99%